2015
DOI: 10.1007/s10278-015-9850-0
|View full text |Cite
|
Sign up to set email alerts
|

Stakeholders’ Perceptions Regarding the Use of Patient Photographs Integrated with Medical Imaging Studies

Abstract: Integrating digital facial photographs of pediatric patients as identifiers (ID) with medical imaging (integrated photographic IDs) may increase the detection of mislabeled studies. The purpose of this study was to determine how different stakeholders would receive this novel technology. Parents or guardians of patients in a children's hospital outpatient radiology department, radiology faculty and residents, and radiology technologists and nurses were asked to complete a survey. The perception about the antic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…These findings are consistent with prior research of patients' acceptance of photographs for patient identification in pediatrics 7 and acceptance of clinical photographs in teledermatology, radiology, general internal medicine, anesthesiology, and for use in medical education, which demonstrates that patients are generally willing to share their PHI with clinicians, even when they have concerns about privacy and information security. [12][13][14][15][16][17][22][23][24][25][26][27] For example, one study demonstrated that, although 82% of patients had concerns about the security of EHRs, 75% agreed that the benefits of EHRs outweighed the risks to security. 25 Another study revealed that patients were open and willing to share PHI with clinicians, and their comfort with sharing information increased when privacy concerns were addressed by clinicians.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…These findings are consistent with prior research of patients' acceptance of photographs for patient identification in pediatrics 7 and acceptance of clinical photographs in teledermatology, radiology, general internal medicine, anesthesiology, and for use in medical education, which demonstrates that patients are generally willing to share their PHI with clinicians, even when they have concerns about privacy and information security. [12][13][14][15][16][17][22][23][24][25][26][27] For example, one study demonstrated that, although 82% of patients had concerns about the security of EHRs, 75% agreed that the benefits of EHRs outweighed the risks to security. 25 Another study revealed that patients were open and willing to share PHI with clinicians, and their comfort with sharing information increased when privacy concerns were addressed by clinicians.…”
Section: Discussionmentioning
confidence: 99%
“…Among patients enrolled in a pilot study in an ED, 84% had positive attitudes toward the use of clinical photographs for medical education 17 . A survey of parents at a pediatric hospital found that 96% of parents would support the integration of their child’s facial photograph with imaging studies as a strategy to reduce identification errors 16 . However, no study to date has assessed the perceptions of adult patients having their photograph taken upon registration and incorporated into the EHR to improve patient identification.…”
mentioning
confidence: 99%
See 3 more Smart Citations